INSIGHT INTO BIPOLAR DISORDER - Guedes, Ana Clara Medeiros (2023)
The research addressed the topic of insight in bipolar disorder through an exploratory literature review. The objective was to analyze the concept of insight and its relationship with bipolar disorder, as well as to identify factors that influence its development and possible therapeutic approaches. The problem explored was the difficulty in acquiring and maintaining insight into this disorder, a factor that can impact the treatment and prognosis of patients. The results pointed to the importance of the role of the family and the medical team in the development of insight, as well as the use of specific therapeutic interventions, such as Cognitive-Behavioral Therapy, to assist in the construction and maintenance of this process. The methodology used was the analysis of scientific articles and specialized books, allowing a broad understanding of the subject. The contribution of the work to the academic area was to provide theoretical and practical subsidies for professionals who work with patients with bipolar disorder, in addition to stimulating discussions about the importance of insight in this context. It is concluded that insight is a crucial element in the management of bipolar disorder and should be addressed comprehensively in the treatment of these patients.